Police Strategy In Establishing Anti-Corruption Attitudes In Communities In The Legal Territory Of The East Java Regional Police - Nikolas Bagas Yudhi (Universitas Airlangga, 2022)
Polri's strategy in shaping anti-corruption behavior in the community in the jurisdiction of the East Java Police: establishment of the Saber Extortion Task Force, synergizing 3 pillars, conducting anti-corruption character education in the school environment. Barriers to the National Police in shaping anti-corruption behavior in the community in the jurisdiction of the East Java Regional Police include: First, the absence of SOPs in the OTT activities of the Saber Pungli Task Force. Second, the lack of bhabinkamtibmas personnel. Third, the occurrence of the corona virus pandemic so that all face-to-face activities including seminars were also cancelled.